2004
DOI: 10.1017/s1357729800053923
|View full text |Cite
|
Sign up to set email alerts
|

The influence of climatic conditions on physiological and behavioural parameters in dairy cows kept in open stables

Abstract: This study aimed to assess whether cows are able to cope with the range of climatic conditions they are exposed to in open stables on commercial farms in central Europe. On each of four farms, ten lactating cows were observed over a total of five weeks in winter, spring and summer. Based on continuous measurements of air temperature (–13·8 to 28·7ºC) and relative air humidity (0·26 to 0·99), a mean value of a temperature humidity index (THI) was calculated for each farm and each observation day for night and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 19 publications
7
47
0
2
Order By: Relevance
“…Lacourt and Tarrant (1985) report that glycogen reserves can be significantly depleted in animals exposed to pre-slaughter stress, limiting post-mortem glycogenolysis and glycolysis, resulting in meat with an above normal ultimate pH. Our results agree with Knowles (1998), who report higher stress levels in lambs transported during winter, and with Zähner et al (2004), who report an influence of cold weather on the stress response. However, Kadim et al (2008) report significantly higher meat pH for lambs transported in summer.…”
Section: Discussionsupporting
confidence: 91%
“…Lacourt and Tarrant (1985) report that glycogen reserves can be significantly depleted in animals exposed to pre-slaughter stress, limiting post-mortem glycogenolysis and glycolysis, resulting in meat with an above normal ultimate pH. Our results agree with Knowles (1998), who report higher stress levels in lambs transported during winter, and with Zähner et al (2004), who report an influence of cold weather on the stress response. However, Kadim et al (2008) report significantly higher meat pH for lambs transported in summer.…”
Section: Discussionsupporting
confidence: 91%
“…Surprisingly, the cold season was more stressful than the hot season. Cortisol levels were higher in winter, which agrees with Knowles et al (1998) who reported higher cortisol levels in lambs transported during winter, and with Zähner et al (2004), who found an influence of cold climatic conditions on cortisol secretion in dairy cows. However, other authors report increased cortisol values in lambs during summer (Minton and Blecha, 1990;Lowe et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Standing is a common response to heat (Zähner et al 2004;Tucker et al 2008). Nevertheless, in a study undertaken in Texas, USA using 16 pens of 18 m 2 and using two animals per pen, Mitlöhner et al (2001) did not find excessive standing in unshaded pens compared with shaded pens, even though unshaded animals were being heat stressed.…”
Section: Discussionmentioning
confidence: 94%